Sepsis-Associated Acute Kidney Injury: What’s New Regarding Its Diagnostics and Therapeutics? - Dimitris Kounatidis; Ilektra Tzivaki; Stavroula Daskalopoulou; Anna Daskou; Andreas Adamou; Anastasia Rigatou; Evangelos Sdogkos; Irene Karampela; Maria Dalamaga; Natalia G. Vallianou (Diagnostics)
Sepsis-associated acute kidney injury (SA-AKI) is defined as the development of AKI in the context of a potentially life-threatening organ dysfunction attributed to an abnormal immune response to infection. SA-AKI has been associated with increased mortality when compared to sepsis or AKI alone. Therefore, its early recognition is of the utmost importance in terms of its morbidity and mortality rates. The aim of this review is to shed light on the pathophysiological pathways implicated in SA-AKI as well as its diagnostics and therapeutics. In this review, we will elucidate upon serum and urinary biomarkers, such as creatinine, cystatin, neutrophil gelatinase-associated lipocalin (NGAL), proenkephalin A 119–159, interleukin-6, interleukin-8 and interleukin-18, soluble toll-like receptor 2 (sTLR2), chemokine ligand 2 (CCL2) and chemokine C-C-motif 14 (CCL14). In addition, the role of RNA omics as well as machine learning programs for the timely diagnosis of SA-AKI will be further discussed. Moreover, regarding SA-AKI treatment, we will elaborate upon potential therapeutic agents that are being studied, based on the pathophysiology of SA-AKI, in humans and in animal models.